Recent Progress in Data Engineering and Internet Technology Volume 2 - Gaol, Ford Lumban.; Gaol, Ford Lumban. (Lecture Notes in Electrical Engineering,, 2012)
The latest inventions in internet technology influence most of business and daily activities. Internet security, internet data management, web search, data grids, cloud computing, and web-based applications play vital roles, especially in business and industry, as more transactions go online and mobile. Issues related to ubiquitous computing are becoming critical.   Internet technology and data engineering should reinforce efficiency and effectiveness of business processes. These technologies should help people make better and more accurate decisions by presenting necessary information and possible consequences for the decisions. Intelligent information systems should help us better understand and manage information with ubiquitous data repository and cloud computing.   This book is a compilation of some recent research findings in Internet Technology and Data Engineering. This book provides state-of-the-art accounts in computational algorithms/tools, database management and database technologies,  intelligent information systems, data engineering applications,  internet security, internet data management, web search, data grids, cloud computing, web-based application, and other related topics.